Consistency and applicability of return to function guidelines in tactical-athletes with exertional heat illness. A systematic review - O'Reilly, M.; Hu, Y. E.; Gruber, J.; Jones, D. M.; Daniel, A.; Marra, J.; Fraser, J. J. (The Physician and Sportsmedicine, 2023)
Objective To assess the consistency of return to sport and occupation recommendations following EHI provided in published clinical practice guidelines, consensus statements, position statements, and practice alerts. The agreement between medical policies governing the return to duty following EHI between the branches of the United States Armed Forces and published recommendations was assessed.